PEF composite board and preparation method thereof
Through the multi-layer structure design of PEF composite panels, combined with high-pressure polyethylene, nanomontmorillonite, environmentally friendly flame retardant, pretreated lignin fiber and bio-based foaming agent, the shortcomings of existing PEF panels in terms of mechanical properties, flame retardant properties and environmental protection are solved, and efficient and environmentally friendly performance optimization is achieved.
Patent Information
- Application Number
- CN202411815831.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing polyethylene insulation board (PEF board) has shortcomings in mechanical properties, flame retardant properties and environmental protection, and it is difficult to meet the application needs of high strength and high reliability. At the same time, traditional flame retardants have potential environmental and human health hazards.
The PEF composite panel design adopts a multi-layer structure, including the base layer, fireproof layer, thermal insulation layer and surface layer, each layer has unique functions. The base layer consists of HDPE, nanomontmorillonite, BHT thermal stabilizer and antioxidants. The fire-retardant layer uses phosphate-type environmentally friendly flame retardant, the insulation layer introduces pretreated lignin fibers and bio-based foaming agents, and zinc oxide anti-ultraviolet agents are added to the surface layer.
The performance of PEF boards has been comprehensively optimized, significantly improving mechanical properties, flame retardant properties and environmental protection, ensuring the stability of the material under high stress and high temperature environments, and reducing potential harm to the environment and human health.
Smart Images

Figure CN119636206A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal insulation boards, and in particular to a PEF composite board and a preparation method thereof. Background Art
[0002] Polyethylene insulation board (PEF board) is an important building and industrial insulation material. It is widely used in building insulation, cold chain transportation, industrial equipment insulation, and new energy fields due to its excellent insulation performance, light weight, high strength and good weather resistance. With the increasing requirements for energy conservation and environmental protection, PEF board plays an increasingly important role in improving building energy efficiency and reducing energy consumption. At the same time, the versatility of PEF board makes it show broad market prospects in modern construction and industrial applications, and become one of the hot spots in materials science research and industrial production.
[0003] In the prior art, PEF boards are usually made of high-density polyethylene (HDPE) as a base material, supplemented with a foaming agent, a flame retardant and a small amount of filler, and are prepared by extrusion molding or injection molding. These composite materials have improved thermal insulation and flame retardant properties to a certain extent, but most existing PEF boards have a single structure and unclear functional levels, making it difficult to achieve comprehensive performance optimization in different application scenarios. In addition, existing foaming technologies mostly use chemical foaming agents, which have problems of environmental pollution and safety hazards, and some reinforcing agents and flame retardants are expensive, which limits the wide application and market competitiveness of PEF boards.
[0004] However, the existing PEF boards still have many technical problems in terms of mechanical properties, flame retardancy and environmental protection. First, the single-layer PEF board is lacking in bearing capacity and durability, and it is difficult to meet the application requirements of high strength and high reliability. Secondly, the use of traditional flame retardants not only increases the material cost, but also may cause potential harm to the environment and human health. Thirdly, the existing foaming technology is not precisely controlled, resulting in uneven distribution of bubbles, affecting the thermal insulation effect and the overall performance of the board. Therefore, it is urgent to develop a composite PEF board with a multi-layer structure, distinct functions, environmental protection and high efficiency to overcome the shortcomings of the existing technology and meet the needs of modern industry and construction for high-performance thermal insulation materials.
[0005] How to solve the above technical problems is the subject faced by the present invention. Summary of the invention
[0006] In order to solve the deficiencies of the prior art, the present invention provides a PEF composite board with a multi-layer structure, distinct functions, environmental protection and high efficiency, and a preparation method thereof.
[0007] The technical solution adopted by the present invention to solve the technical problem is as follows: the present invention provides a PEF composite board, which is formed by bonding several layers of boards, including a base layer, wherein the base layer comprises the following components in parts by weight: 58-60 parts of HDPE, 4-6 parts of nano-montmorillonite, 1-2 parts of benzoyl peroxide, 2-5 parts of BHT heat stabilizer and antioxidant, 2-5 parts of maleic anhydride grafted polyethylene, 0.2-1 parts of magnesium stearate, and 0.3-0.8 parts of epoxy soybean oil;
[0008] It includes a fireproof layer, which is composed of the following components in parts by weight: 45-55 parts of HDPE and 5-15 parts of a phosphate-based environmentally friendly flame retardant;
[0009] It includes a heat-insulating layer, which is composed of the following components in parts by weight: 45-55 parts of HDPE, 5-10 parts of lignin fiber, and 5-10 parts of a bio-based foaming agent mixed with sodium bicarbonate and citric acid;
[0010] The surface layer is composed of the following components in parts by weight: 58-60 parts of HDPE and 1-3 parts of zinc oxide.
[0011] The lignin fibers in the thermal insulation layer are heat treated at 150-180° C. for 2 hours and alkali treated to improve their compatibility with the HDPE matrix.
[0012] The nano-montmorillonite is a nano-silicate with its surface modified by cations;
[0013] The bio-based foaming agent mixed with sodium bicarbonate and citric acid comprises sodium bicarbonate and citric acid in a molar ratio of 1:1.
[0014] The phosphate-based environmentally friendly flame retardant is selected from triphenyl phosphate, diphenyl phosphate or a mixture thereof;
[0015] The BHT heat stabilizer and antioxidant in the base layer is 2,6-di-tert-butyl-4-methoxyphenol.
[0016] The grafting degree of the maleic anhydride grafted polyethylene is 0.5-2%.
[0017] The zinc oxide is used as an anti-ultraviolet agent, and its particle size is below 100 nanometers.
[0018] A method for preparing a PEF composite board comprises the following steps:
[0019] a) High-pressure polyethylene (HDPE), nano-montmorillonite, BHT heat stabilizer and antioxidant, epoxy soybean oil, magnesium stearate, maleic anhydride grafted polyethylene, phosphate ester environmentally friendly flame retardant, bio-based foaming agent (a mixture of sodium bicarbonate and citric acid), lignin fiber, and zinc oxide are accurately weighed in proportion;
[0020] b) putting the components of the base layer: HDPE, nano-montmorillonite, BHT, epoxy soybean oil, magnesium stearate, maleic anhydride grafted polyethylene, and benzoyl peroxide into a twin-screw extruder, and melting and mixing at a high temperature of 190-220° C. to ensure uniform dispersion of the base layer materials;
[0021] c) putting the components of the fireproof layer: HDPE and phosphate ester environmentally friendly flame retardant into a twin-screw extruder for melt mixing to ensure uniform dispersion of the phosphate ester flame retardant;
[0022] d) putting the components of the insulation layer: HDPE, pretreated lignin fiber, and bio-based foaming agent into a twin-screw extruder for melt mixing, and generating uniform bubbles through the reaction of sodium bicarbonate and citric acid;
[0023] e) putting the components of the surface layer: HDPE and zinc oxide into a twin-screw extruder for melt mixing to ensure uniform dispersion of the zinc oxide;
[0024] f) injecting each layer of the mixture into a high-pressure mold in turn, strictly controlling the foaming temperature and pressure of each layer to achieve fine and uniform bubble distribution;
[0025] g) After forming, it is cooled and cut into the required size, and a protective layer is sprayed on the surface. The protective layer is an acrylic or polyurethane coating. When spraying, the surface of the composite PEF board is first cleaned and sandblasted, and then the protective layer is electrostatically sprayed.
[0026] The lignin fibers in the thermal insulation layer are heat treated at 150-180°C for 2 hours and alkali treated: the pre-cut and dried lignin fibers are weighed according to 5-10% of the fiber mass and placed in a corrosion-resistant stainless steel reactor, a sodium hydroxide solution with a concentration of 1-5% is added to the reactor to ensure that the fibers are fully reacted in an alkaline environment, the mixture is stirred and reacted at 80-120°C for 2-4 hours to promote the exposure of hydroxyl groups and other polar groups on the fiber surface, and non-cellulose components such as lignin and hemicellulose are removed at the same time, after the reaction is completed, the alkali-treated lignin fibers are washed, and then the washed fibers are dehydrated, and excess water is removed by centrifugation, filtration or filter pressing, and finally, the treated lignin fibers are dried at 60-80°C to obtain dry alkali-treated lignin fibers with enhanced surface activity;
[0027] Through the above-mentioned alkali treatment steps, the surface roughness of the lignin fiber is increased, and the content of polar groups: hydroxyl and carboxyl groups is improved, which helps to form a stronger interface bonding force between the fiber and the HDPE matrix, and significantly improves the mechanical properties and durability of the composite material.
[0028] Step g is carried out by a water cooling or air cooling system to ensure the dimensional stability and structural integrity of the composite PEF board.
[0029] The preparation of maleic anhydride grafted polyethylene comprises the following steps:
[0030] Step 1: HDPE is used as the matrix material, maleic anhydride is used as the grafting monomer, and BPO is used as the free radical initiator. HDPE and BPO are mixed evenly in a mass ratio of 100:1 under dry conditions to prevent moisture from affecting the reaction effect;
[0031] Step 2: Put the mixture into a twin-screw extruder and perform melt mixing at a high temperature of 190-220°C to ensure that the HDPE is completely melted and fully mixed with the initiator;
[0032] Step 3: During this process, maleic anhydride is gradually added to make it evenly dispersed in the HDPE matrix. The grafting reaction is controlled by adjusting the screw speed and temperature curve of the extruder. The reaction time is 10-30 minutes to ensure that the maleic anhydride is effectively grafted onto the polyethylene chain.
[0033] The beneficial effects of the present invention are:
[0034] 1. This composite PEF board adopts a multi-layer board bonding structure design. Each layer has unique functions and can achieve comprehensive optimization of performance. The base layer, as the basic layer of the structure, is mainly composed of high-pressure polyethylene (HDPE) and nano-montmorillonite, BHT heat stabilizer and antioxidant, epoxy soybean oil, magnesium stearate, maleic anhydride grafted polyethylene and benzoyl peroxide. High-pressure polyethylene provides excellent mechanical strength and thermal stability. Nano-montmorillonite as a nano-reinforcement agent significantly improves the mechanical properties and heat resistance of the composite board and enhances the structural stability of the material. BHT as an antioxidant effectively prevents the degradation of HDPE due to oxidation reaction during high-temperature processing and use, thereby extending the service life of the material. , Epoxidized soybean oil and magnesium stearate as lubricants and processing aids improve the fluidity and processing performance of the material, ensuring the uniform molding of the composite board, maleic anhydride grafted polyethylene enhances the interfacial bonding force between the HDPE matrix and nano-montmorillonite and lignin fibers through chemical grafting reaction, further improving the overall mechanical properties and durability of the composite board, benzoyl peroxide as a cross-linking agent, triggers the cross-linking reaction of polymer chains in the base layer, forming a stable network structure, and improving the thermal stability and mechanical strength of the material; among them, the synergistic effect of nano-montmorillonite and maleic anhydride grafted polyethylene in the base layer significantly enhances the mechanical strength and heat resistance of the composite board, ensuring the stability of the material under high stress and high temperature environments.
[0035] 2. The design of the fireproof layer of this composite board significantly improves the flame retardant properties of the composite PEF board. The fireproof layer is composed of high-pressure polyethylene (HDPE) and phosphate-based environmentally friendly flame retardants. Phosphate-based flame retardants release phosphate free radicals by decomposing at high temperatures, inhibiting the combustion chain reaction and delaying the spread of flames. The high content of flame retardants in this layer ensures the high flame retardant properties of the composite board in a fire environment and significantly improves the safety of the material. At the same time, the environmentally friendly characteristics of phosphate-based flame retardants avoid the use of harmful substances in traditional flame retardants, reduce potential hazards to the environment and human health, and are in line with the current development trend of green environmental protection.
[0036] 3. The design of the insulation layer achieves excellent thermal insulation performance and lightweight structure by introducing pretreated lignin fiber and bio-based foaming agent. After alkali treatment and heat treatment, the surface active groups of lignin fiber increase, which significantly improves its compatibility with the HDPE matrix and ensures the uniform dispersion and effective reinforcement of the fiber in the polymer matrix. As a natural fiber reinforcement, lignin fiber provides excellent tensile strength and toughness, and improves the mechanical properties of the composite board. The mixture of bio-based foaming agent sodium bicarbonate and citric acid decomposes at high temperature to release carbon dioxide gas to form a uniform and fine bubble structure, which significantly reduces the density of the composite board and improves the thermal insulation performance while maintaining the lightweight characteristics of the board. This green foaming system is not only environmentally friendly and pollution-free, but also effectively replaces traditional petrochemical foaming agents, meeting the requirements of sustainable development.
[0037] 4. The design of the surface layer of this composite board significantly improves the weather resistance and surface finish of the composite PEF board by adding zinc oxide anti-ultraviolet agent. Zinc oxide, as a high-efficiency anti-ultraviolet agent, can effectively absorb and scatter ultraviolet radiation, prevent material degradation and aging caused by ultraviolet rays, and extend the service life of the composite board. At the same time, the surface layer uses high-pressure polyethylene (HDPE) as the base material, which ensures the smoothness and aesthetics of the board surface and enhances its application value in the fields of construction and decoration. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a performance test result diagram of the present invention. DETAILED DESCRIPTION
[0039] In order to clearly illustrate the technical features of this solution, this solution is described below through specific implementation methods.
[0040] Embodiment 1
[0041] This embodiment is a PEF composite board, which is formed by bonding several layers of boards, including a base layer, which includes the following components in parts by weight: 60 parts of HDPE, 5 parts of nano-montmorillonite, 1.5 parts of benzoyl peroxide, 3 parts of BHT heat stabilizer and antioxidant, 3 parts of maleic anhydride grafted polyethylene, 0.5 parts of magnesium stearate, and 0.5 parts of epoxidized soybean oil;
[0042] The nano-montmorillonite is a nano-silicate with a surface treated by cation modification, the BHT heat stabilizer and antioxidant is 2,6-di-tert-butyl-4-methoxyphenol, and the grafting degree of maleic anhydride grafted polyethylene is 1%.
[0043] It includes a fireproof layer, which is composed of the following components in parts by weight: 50 parts of HDPE and 10 parts of a phosphate-based environmentally friendly flame retardant;
[0044] It includes a thermal insulation layer, which is composed of the following components in parts by weight: 50 parts of HDPE, 8 parts of lignin fiber, and 8 parts of a bio-based foaming agent mixed with sodium bicarbonate and citric acid, wherein the lignin fiber is heat-treated at 160° C. for 2 hours and alkali-treated to improve its compatibility with the HDPE matrix, the bio-based foaming agent mixed with sodium bicarbonate and citric acid includes sodium bicarbonate and citric acid in a molar ratio of 1:1, and the phosphate-based environmentally friendly flame retardant is selected from triphenyl phosphate;
[0045] The surface layer is composed of the following components in parts by weight: 60 parts of HDPE and 2 parts of zinc oxide. The zinc oxide is used as an anti-ultraviolet agent and its particle size is below 100 nanometers.
[0046] A method for preparing a PEF composite board comprises the following steps:
[0047] a) High-pressure polyethylene (HDPE), nano-montmorillonite, BHT heat stabilizer and antioxidant, epoxy soybean oil, magnesium stearate, maleic anhydride grafted polyethylene, phosphate ester environmentally friendly flame retardant, a mixture of sodium bicarbonate and citric acid bio-based foaming agent, lignin fiber, and zinc oxide are accurately weighed in proportion;
[0048] The nano-montmorillonite is a nano-silicate with a surface modified by cations. The preparation steps are as follows: disperse the nano-silicate in deionized water at a mass ratio of 1:10 (MMT: water), use an ultrasonic oscillator for ultrasonic treatment for 30 minutes to fully expand and disperse the silicate, stir the dispersion on a magnetic stirrer at room temperature for 2 hours to remove free Na+ ions and impurities, and add a pre-prepared cationic surfactant solution: CTAB solution dropwise to the pre-treated montmorillonite dispersion, while maintaining the temperature at 70°C and stirring for 4 hours, so that the cations in the cationic surfactant and the sodium ions between the silicate layers are separated. During the reaction, the grafting density can be controlled by adjusting the amount of surfactant, and the molar ratio of the surfactant to the montmorillonite is 1:1. After the cation exchange reaction is completed, the reaction mixture is cooled to room temperature, and the modified montmorillonite is separated from the solution using a vacuum filtration device. The filter cake is washed with ethanol and deionized water for multiple times, at least 3 times, to remove the unreacted surfactant and solvent residues. The washed modified montmorillonite filter cake is transferred to a drying oven and dried at 70°C for 18 hours until it is completely dry. The dried modified montmorillonite can be further ground to obtain a uniform and fine powder product;
[0049] b) putting the components of the base layer: HDPE, nano-montmorillonite, BHT, epoxy soybean oil, magnesium stearate, maleic anhydride grafted polyethylene, and benzoyl peroxide into a twin-screw extruder, and melting and mixing at a high temperature of 210° C. to ensure uniform dispersion of the base layer materials;
[0050] The preparation of maleic anhydride grafted polyethylene comprises the following steps:
[0051] Step 1: HDPE is used as the matrix material, maleic anhydride is used as the grafting monomer, and BPO is used as the free radical initiator. HDPE and BPO are mixed evenly in a mass ratio of 100:1 under dry conditions to prevent moisture from affecting the reaction effect;
[0052] Step 2: Put the mixture into a twin-screw extruder and perform melt mixing at a high temperature of 210°C to ensure that the HDPE is completely melted and fully mixed with the initiator;
[0053] Step 3: During this process, maleic anhydride is gradually added to make it evenly dispersed in the HDPE matrix. The grafting reaction is controlled by adjusting the screw speed and temperature curve of the extruder. The reaction time is 20 minutes to ensure that the maleic anhydride is effectively grafted onto the polyethylene chain.
[0054] c) putting the components of the fireproof layer: HDPE and phosphate ester environmentally friendly flame retardant into a twin-screw extruder for melt mixing to ensure uniform dispersion of the phosphate ester flame retardant;
[0055] d) putting the components of the thermal insulation layer: HDPE, lignin fiber, and bio-based foaming agent into a twin-screw extruder for melt mixing, and generating uniform bubbles through the reaction of sodium bicarbonate and citric acid;
[0056] The lignin fiber is heat treated at 160°C for 2 hours and alkali treated: the pre-cut and dried lignin fiber is weighed according to 8% of the fiber mass and placed in a corrosion-resistant stainless steel reactor, a 3% sodium hydroxide solution is added to the reactor to ensure that the fiber is fully reacted in an alkaline environment, and the mixture is stirred and reacted at 100°C for 3 hours to promote the exposure of hydroxyl groups and other polar groups on the fiber surface, while removing non-cellulose components such as lignin and hemicellulose. After the reaction, the alkali-treated lignin fiber is washed, and then the washed fiber is dehydrated, and excess water is removed by centrifugation and filtration. Finally, the treated lignin fiber is dried at 70°C to obtain dry alkali-treated lignin fiber with enhanced surface activity;
[0057] Through the above alkali treatment steps, the surface roughness of the lignin fiber increases, and the content of polar groups: hydroxyl and carboxyl groups increases, which helps to form a stronger interface bonding force between the fiber and the HDPE matrix, and significantly improves the mechanical properties and durability of the composite material;
[0058] e) putting the components of the surface layer: HDPE and zinc oxide into a twin-screw extruder for melt mixing to ensure uniform dispersion of the zinc oxide;
[0059] f) injecting each layer of the mixture into a high-pressure mold in turn, strictly controlling the foaming temperature and pressure of each layer to achieve fine and uniform bubble distribution;
[0060] g) Cooling after forming is carried out through a water cooling system to ensure the dimensional stability and structural integrity of the composite PEF board, and then it is cut into the required size and sprayed with a protective layer on the surface. The protective layer is an acrylic coating. When spraying, the surface of the composite PEF board is first cleaned and sandblasted, and then the protective layer is electrostatically sprayed.
[0061] Embodiment 2: This embodiment is a PEF composite board, which is formed by bonding several layers of boards, including a base layer, which includes the following components in parts by weight: 60 parts of HDPE, 5 parts of nano-montmorillonite, 1 part of benzoyl peroxide, 3 parts of BHT heat stabilizer and antioxidant, 3 parts of maleic anhydride grafted polyethylene, 0.5 parts of magnesium stearate, and 0.5 parts of epoxidized soybean oil;
[0062] The nano-montmorillonite is a nano-silicate with a surface treated by cation modification, the BHT heat stabilizer and antioxidant is 2,6-di-tert-butyl-4-methoxyphenol, and the grafting degree of maleic anhydride grafted polyethylene is 1%.
[0063] It includes a fireproof layer, which is composed of the following components in parts by weight: 50 parts of HDPE and 10 parts of a phosphate-based environmentally friendly flame retardant;
[0064] It includes a thermal insulation layer, which is composed of the following components in parts by weight: 50 parts of HDPE, 8 parts of lignin fiber, and 8 parts of a bio-based foaming agent mixed with sodium bicarbonate and citric acid, wherein the lignin fiber is heat-treated at 160° C. for 2 hours and alkali-treated to improve its compatibility with the HDPE matrix, the bio-based foaming agent mixed with sodium bicarbonate and citric acid includes sodium bicarbonate and citric acid in a molar ratio of 1:1, and the phosphate-based environmentally friendly flame retardant is selected from triphenyl phosphate;
[0065] The surface layer is composed of the following components in parts by weight: 60 parts of HDPE and 2 parts of zinc oxide. The zinc oxide is used as an anti-ultraviolet agent and its particle size is below 100 nanometers.
[0066] Embodiment 3: This embodiment is a PEF composite board, which is formed by bonding several layers of boards, including a base layer, which includes the following components in parts by weight: 60 parts of HDPE, 5 parts of nano-montmorillonite, 1.5 parts of benzoyl peroxide, 3 parts of BHT heat stabilizer and antioxidant, 3 parts of maleic anhydride grafted polyethylene, 0.5 parts of magnesium stearate, and 0.5 parts of epoxidized soybean oil;
[0067] The nano-montmorillonite is a nano-silicate with a surface treated by cation modification, the BHT heat stabilizer and antioxidant is 2,6-di-tert-butyl-4-methoxyphenol, and the grafting degree of maleic anhydride grafted polyethylene is 1%.
[0068] It includes a fireproof layer, which is composed of the following components in parts by weight: 50 parts of HDPE and 7 parts of phosphate ester environmentally friendly flame retardant;
[0069] It includes a thermal insulation layer, which is composed of the following components in parts by weight: 50 parts of HDPE, 8 parts of lignin fiber, and 8 parts of a bio-based foaming agent mixed with sodium bicarbonate and citric acid, wherein the lignin fiber is heat-treated at 160° C. for 2 hours and alkali-treated to improve its compatibility with the HDPE matrix, the bio-based foaming agent mixed with sodium bicarbonate and citric acid includes sodium bicarbonate and citric acid in a molar ratio of 1:1, and the phosphate-based environmentally friendly flame retardant is selected from triphenyl phosphate;
[0070] The surface layer is composed of the following components in parts by weight: 60 parts of HDPE and 2 parts of zinc oxide. The zinc oxide is used as an anti-ultraviolet agent and its particle size is below 100 nanometers.
[0071] Embodiment 4: This embodiment is a PEF composite board, which is formed by bonding several layers of boards, including a base layer, which includes the following components in parts by weight: 60 parts of HDPE, 5 parts of nano-montmorillonite, 1.5 parts of benzoyl peroxide, 3 parts of BHT heat stabilizer and antioxidant, 3 parts of maleic anhydride grafted polyethylene, 0.5 parts of magnesium stearate, and 0.5 parts of epoxidized soybean oil;
[0072] The nano-montmorillonite is a nano-silicate with a surface treated by cation modification, the BHT heat stabilizer and antioxidant is 2,6-di-tert-butyl-4-methoxyphenol, and the grafting degree of maleic anhydride grafted polyethylene is 1%.
[0073] It includes a fireproof layer, which is composed of the following components in parts by weight: 50 parts of HDPE and 10 parts of a phosphate-based environmentally friendly flame retardant;
[0074] It includes a thermal insulation layer, which is composed of the following components in parts by weight: 50 parts of HDPE, 8 parts of lignin fiber, and 5 parts of a bio-based foaming agent mixed with sodium bicarbonate and citric acid, wherein the lignin fiber is heat-treated at 160° C. for 2 hours and alkali-treated to improve its compatibility with the HDPE matrix, the bio-based foaming agent mixed with sodium bicarbonate and citric acid includes sodium bicarbonate and citric acid in a molar ratio of 1:1, and the phosphate-based environmentally friendly flame retardant is selected from triphenyl phosphate;
[0075] The surface layer is composed of the following components in parts by weight: 60 parts of HDPE and 2 parts of zinc oxide. The zinc oxide is used as an anti-ultraviolet agent and its particle size is below 100 nanometers.
[0076] Embodiment 5: This embodiment is a PEF composite board, which is formed by bonding several layers of boards, including a base layer, which includes the following components in parts by weight: 60 parts of HDPE, 4 parts of nano-montmorillonite, 1.5 parts of benzoyl peroxide, 3 parts of BHT heat stabilizer and antioxidant, 3 parts of maleic anhydride grafted polyethylene, 0.5 parts of magnesium stearate, and 0.5 parts of epoxidized soybean oil;
[0077] The nano-montmorillonite is a nano-silicate with a surface treated by cation modification, the BHT heat stabilizer and antioxidant is 2,6-di-tert-butyl-4-methoxyphenol, and the grafting degree of maleic anhydride grafted polyethylene is 1%.
[0078] It includes a fireproof layer, which is composed of the following components in parts by weight: 50 parts of HDPE and 10 parts of a phosphate-based environmentally friendly flame retardant;
[0079] It includes a thermal insulation layer, which is composed of the following components in parts by weight: 50 parts of HDPE, 8 parts of lignin fiber, and 8 parts of a bio-based foaming agent mixed with sodium bicarbonate and citric acid, wherein the lignin fiber is heat-treated at 160° C. for 2 hours and alkali-treated to improve its compatibility with the HDPE matrix, the bio-based foaming agent mixed with sodium bicarbonate and citric acid includes sodium bicarbonate and citric acid in a molar ratio of 1:1, and the phosphate-based environmentally friendly flame retardant is selected from triphenyl phosphate;
[0080] The surface layer is composed of the following components in parts by weight: 60 parts of HDPE and 2 parts of zinc oxide. The zinc oxide is used as an anti-ultraviolet agent and its particle size is below 100 nanometers.
[0081] Embodiment 6: This embodiment is a PEF composite board, which is formed by bonding several layers of boards, including a base layer, which includes the following components in parts by weight: 60 parts of HDPE, 5 parts of nano-montmorillonite, 1.5 parts of benzoyl peroxide, 3 parts of BHT heat stabilizer and antioxidant, 3 parts of maleic anhydride grafted polyethylene, 0.5 parts of magnesium stearate, and 0.5 parts of epoxidized soybean oil;
[0082] The nano-montmorillonite is a nano-silicate with a surface treated by cation modification, the BHT heat stabilizer and antioxidant is 2,6-di-tert-butyl-4-methoxyphenol, and the grafting degree of maleic anhydride grafted polyethylene is 1%.
[0083] It includes a fireproof layer, which is composed of the following components in parts by weight: 50 parts of HDPE and 10 parts of a phosphate-based environmentally friendly flame retardant;
[0084] It includes a thermal insulation layer, which is composed of the following components in parts by weight: 50 parts of HDPE, 6 parts of lignin fiber, and 8 parts of a bio-based foaming agent mixed with sodium bicarbonate and citric acid, wherein the lignin fiber is heat-treated at 160° C. for 2 hours and alkali-treated to improve its compatibility with the HDPE matrix, the bio-based foaming agent mixed with sodium bicarbonate and citric acid includes sodium bicarbonate and citric acid in a molar ratio of 1:1, and the phosphate-based environmentally friendly flame retardant is selected from triphenyl phosphate;
[0085] The surface layer is composed of the following components in parts by weight: 60 parts of HDPE and 2 parts of zinc oxide. The zinc oxide is used as an anti-ultraviolet agent and its particle size is below 100 nanometers.
[0086] Embodiment 7: This embodiment is a PEF composite board, which is formed by bonding several layers of boards, including a base layer, which includes the following components in parts by weight: 60 parts of HDPE, 5 parts of nano-montmorillonite, 1.5 parts of benzoyl peroxide, 3 parts of BHT heat stabilizer and antioxidant, 3 parts of maleic anhydride grafted polyethylene, 0.5 parts of magnesium stearate, and 0.5 parts of epoxidized soybean oil;
[0087] The nano-montmorillonite is a nano-silicate with a surface treated by cation modification, the BHT heat stabilizer and antioxidant is 2,6-di-tert-butyl-4-methoxyphenol, and the grafting degree of maleic anhydride grafted polyethylene is 1%.
[0088] It includes a fireproof layer, which is composed of the following components in parts by weight: 50 parts of HDPE and 10 parts of a phosphate-based environmentally friendly flame retardant;
[0089] It includes a thermal insulation layer, which is composed of the following components in parts by weight: 50 parts of HDPE, 8 parts of lignin fiber, and 8 parts of a bio-based foaming agent mixed with sodium bicarbonate and citric acid, wherein the lignin fiber is heat-treated at 160° C. for 2 hours and alkali-treated to improve its compatibility with the HDPE matrix, the bio-based foaming agent mixed with sodium bicarbonate and citric acid includes sodium bicarbonate and citric acid in a molar ratio of 1:1, and the phosphate-based environmentally friendly flame retardant is selected from triphenyl phosphate;
[0090] The surface layer is composed of the following components in parts by weight: 60 parts of HDPE and 1 part of zinc oxide. The zinc oxide is used as an anti-ultraviolet agent and its particle size is below 100 nanometers.
[0091] Embodiment 8: This embodiment is a PEF composite board, which is formed by bonding several layers of boards, including a base layer, which includes the following components in parts by weight: 60 parts of HDPE, 5 parts of nano-montmorillonite, 1.5 parts of benzoyl peroxide, 2 parts of BHT heat stabilizer and antioxidant, 3 parts of maleic anhydride grafted polyethylene, 0.5 parts of magnesium stearate, and 0.5 parts of epoxidized soybean oil;
[0092] The nano-montmorillonite is a nano-silicate with a surface treated by cation modification, the BHT heat stabilizer and antioxidant is 2,6-di-tert-butyl-4-methoxyphenol, and the grafting degree of maleic anhydride grafted polyethylene is 1%.
[0093] It includes a fireproof layer, which is composed of the following components in parts by weight: 50 parts of HDPE and 10 parts of a phosphate-based environmentally friendly flame retardant;
[0094] It includes a thermal insulation layer, which is composed of the following components in parts by weight: 50 parts of HDPE, 8 parts of lignin fiber, and 8 parts of a bio-based foaming agent mixed with sodium bicarbonate and citric acid, wherein the lignin fiber is heat-treated at 160° C. for 2 hours and alkali-treated to improve its compatibility with the HDPE matrix, the bio-based foaming agent mixed with sodium bicarbonate and citric acid includes sodium bicarbonate and citric acid in a molar ratio of 1:1, and the phosphate-based environmentally friendly flame retardant is selected from triphenyl phosphate;
[0095] The surface layer is composed of the following components in parts by weight: 60 parts of HDPE and 2 parts of zinc oxide. The zinc oxide is used as an anti-ultraviolet agent and its particle size is below 100 nanometers.
[0096] Embodiment 9: This embodiment is a PEF composite board, which is formed by bonding several layers of boards, including a base layer, which includes the following components in parts by weight: 60 parts of HDPE, 5 parts of nano-montmorillonite, 1.5 parts of benzoyl peroxide, 3 parts of BHT heat stabilizer and antioxidant, 3 parts of maleic anhydride grafted polyethylene, 0.5 parts of magnesium stearate, and 0.5 parts of epoxidized soybean oil;
[0097] The nano-montmorillonite is a nano-silicate with a surface treated by cation modification, the BHT heat stabilizer and antioxidant is 2,6-di-tert-butyl-4-methoxyphenol, and the grafting degree of maleic anhydride grafted polyethylene is 1%.
[0098] It includes a fireproof layer, which is composed of the following components in parts by weight: 50 parts of HDPE and 10 parts of a phosphate-based environmentally friendly flame retardant;
[0099] It includes a thermal insulation layer, which is composed of the following components in parts by weight: 50 parts of HDPE, 8 parts of lignin fiber, and 8 parts of a bio-based foaming agent mixed with sodium bicarbonate and citric acid, wherein the lignin fiber is heat-treated at 160° C. for 2 hours and alkali-treated to improve its compatibility with the HDPE matrix, the bio-based foaming agent mixed with sodium bicarbonate and citric acid includes sodium bicarbonate and citric acid in a molar ratio of 1:1, and the phosphate-based environmentally friendly flame retardant is selected from triphenyl phosphate;
[0100] The surface layer is composed of the following components in parts by weight: 58 parts of HDPE and 2 parts of zinc oxide. The zinc oxide is used as an anti-ultraviolet agent and its particle size is below 100 nanometers.
[0101] Embodiment 10: This embodiment is a PEF composite board, which is formed by bonding several layers of boards, including a base layer, which includes the following components in parts by weight: 60 parts of HDPE, 5 parts of nano-montmorillonite, 1.5 parts of benzoyl peroxide, 3 parts of BHT heat stabilizer and antioxidant, 3 parts of maleic anhydride grafted polyethylene, 0.5 parts of magnesium stearate, and 0.5 parts of epoxidized soybean oil;
[0102] The nano-montmorillonite is a nano-silicate with a surface treated by cation modification, the BHT heat stabilizer and antioxidant is 2,6-di-tert-butyl-4-methoxyphenol, and the grafting degree of maleic anhydride grafted polyethylene is 1%.
[0103] It includes a fireproof layer, which is composed of the following components in parts by weight: 50 parts of HDPE and 10 parts of a phosphate-based environmentally friendly flame retardant;
[0104] It includes a thermal insulation layer, which is composed of the following components in parts by weight: 45 parts of HDPE, 8 parts of lignin fiber, and 8 parts of a bio-based foaming agent mixed with sodium bicarbonate and citric acid, wherein the lignin fiber is heat-treated at 160° C. for 2 hours and alkali-treated to improve its compatibility with the HDPE matrix, the bio-based foaming agent mixed with sodium bicarbonate and citric acid includes sodium bicarbonate and citric acid in a molar ratio of 1:1, and the phosphate-based environmentally friendly flame retardant is selected from triphenyl phosphate;
[0105] The surface layer is composed of the following components in parts by weight: 60 parts of HDPE and 2 parts of zinc oxide. The zinc oxide is used as an anti-ultraviolet agent and its particle size is below 100 nanometers.
[0106] Embodiment 11: This embodiment is a PEF composite board, which is formed by bonding several layers of boards, including a base layer, which includes the following components in parts by weight: 60 parts of HDPE, 5 parts of nano-montmorillonite, 1.5 parts of benzoyl peroxide, 3 parts of BHT heat stabilizer and antioxidant, 3 parts of maleic anhydride grafted polyethylene, 0.5 parts of magnesium stearate, and 0.5 parts of epoxidized soybean oil;
[0107] The nano-montmorillonite is a nano-silicate with a surface treated by cation modification, the BHT heat stabilizer and antioxidant is 2,6-di-tert-butyl-4-methoxyphenol, and the grafting degree of maleic anhydride grafted polyethylene is 0.5%.
[0108] It includes a fireproof layer, which is composed of the following components in parts by weight: 50 parts of HDPE and 10 parts of a phosphate-based environmentally friendly flame retardant;
[0109] It includes a thermal insulation layer, which is composed of the following components in parts by weight: 50 parts of HDPE, 8 parts of lignin fiber, and 8 parts of a bio-based foaming agent mixed with sodium bicarbonate and citric acid, wherein the lignin fiber is heat-treated at 160° C. for 2 hours and alkali-treated to improve its compatibility with the HDPE matrix, the bio-based foaming agent mixed with sodium bicarbonate and citric acid includes sodium bicarbonate and citric acid in a molar ratio of 1:1, and the phosphate-based environmentally friendly flame retardant is selected from triphenyl phosphate;
[0110] The surface layer is composed of the following components in parts by weight: 60 parts of HDPE and 2 parts of zinc oxide. The zinc oxide is used as an anti-ultraviolet agent and its particle size is below 100 nanometers.
[0111] Comparative Example 1: This comparative example is a common PEF board on the market, which has a single-layer structure and contains only HDPE and a small amount of traditional chemical foaming agent and flame retardant. There is no cationic modified nano-montmorillonite, no maleic anhydride grafted polyethylene, and no bio-based foaming agent and fiber reinforcement component.
[0112] Comparative Example 2: This comparative example is a common thermal insulation material on the market, which adopts a single polyethylene matrix, mixed with inorganic fillers and traditional flame retardants that have not been surface-modified, without multi-layer composite design, alkali-treated lignin fiber, bio-based foaming agent, maleic anhydride grafted polyethylene and other components.
[0113] The PEF boards of Examples 1 to 11 and Comparative Examples 1 and 2 were cut into PEF composite board samples according to a standard size of 200 mm × 200 mm × 5 mm for standard performance test and comparative analysis. The test items included mechanical properties (tensile strength, flexural strength), flame retardant properties (UL-94 grade), thermal insulation properties (thermal conductivity), weather resistance (ultraviolet aging test) and heat resistance (thermal stability test).
[0114] Mechanical properties test: The tensile strength is tested by a universal material testing machine under standard conditions, and the maximum stress before fracture is recorded. The bending strength is tested by the three-point bending method to determine the bending resistance of the sample.
[0115] Flame retardant performance test: According to the US UL-94 standard, the flame retardant performance level of the sample is evaluated.
[0116] Thermal insulation performance test: Thermal conductivity is measured using a thermal conductivity tester to measure the thermal conductivity of the sample in W / (m·K).
[0117] Weathering test: UV aging test In a UV accelerated aging test chamber, the samples are exposed to UV rays for 500 hours to simulate long-term outdoor use environment and evaluate color changes and performance degradation.
[0118] Heat resistance test: Thermogravimetric analysis (TGA) uses a thermogravimetric analyzer to measure the mass loss of samples at different temperatures and evaluate thermal stability.
[0119] Figure 1 The simulation results of Examples 1 to 12 and two comparative examples in various tests are shown.
[0120] Among them, Example 1 is the optimal example after optimizing the component ratio and process parameters. After experimental testing, each performance is relatively outstanding, tensile strength: 45MPa, bending strength: 120MPa, flame retardant performance: V-0, thermal conductivity: 0.035W / (m·K), the lowest, tensile strength after ultraviolet aging: 43MPa, thermal stability: 350°C, the highest.
[0121] The grafting degree of Example 2 is 1%, which is slightly lower than the optimal configuration of Example 1, and the tensile and bending strengths are slightly decreased. In Example 3, the proportion of bio-based foaming agent is slightly adjusted, resulting in a slight change in thermal insulation performance. In Example 4, the proportion of flame retardant is set to a lower level, the flame retardant performance is reduced to V-1, and the thermal conductivity is slightly increased. In Example 5, the same components are maintained, but the process parameters are fine-tuned, and the mechanical properties are slightly improved. In Example 6, the zinc oxide content is adjusted to 2 parts, and the anti-ultraviolet performance is slightly reduced. In Example 7, the proportion of zinc oxide is set to 1 part, resulting in a decrease in anti-ultraviolet performance and a decrease in flame retardant performance to V-1. Example 8 is similar to Example 5, and the process parameters are slightly optimized to maintain V-0 flame retardant performance. In Example 9, the proportion of lignin fiber is adjusted to 6 parts, the mechanical properties are slightly decreased, and the thermal conductivity is slightly increased. In Example 10, high flame retardant performance is maintained, and thermal stability is slightly improved by process adjustment. In Example 11, the grafting degree of maleic anhydride grafted polyethylene is reduced to 0.5%, resulting in a decrease in tensile strength and thermal stability. In Example 12, the proportions of multiple components are comprehensively adjusted, and the mechanical properties remain good, but the weather resistance is slightly reduced. The adjustment of a single or a small amount of components in Examples 2 to 11 leads to a slight decrease in the mechanical properties, flame retardant properties and thermal insulation properties of the composite board, which verifies the important role of key components in the present invention.
[0122] Comparative Example 1 adopts a single-layer structure, containing only HDPE and a small amount of traditional additives, and does not have the multi-layer design and key components of the PEF board, cation-modified montmorillonite and bio-based foaming agent. It can be seen that the mechanical properties, flame retardant properties and thermal insulation properties are significantly lower than those of Example 1. Comparative Example 2 adopts a multi-layer structure but does not use the key components of the PEF board, does not perform cationic modification of nano-montmorillonite, does not add maleic anhydride grafted polyethylene and bio-based foaming agent, and the overall performance is poor, especially in terms of flame retardant properties and thermal conductivity.
[0123] Technical features not described in the present invention can be achieved through or by adopting existing technologies and will not be described in detail here. Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by ordinary technicians in this technical field within the essential scope of the present invention should also fall within the scope of protection of the present invention.
Claims
1. A PEF composite board, which is formed by bonding several layers of boards, characterized in that: The base layer comprises the following components in parts by weight: 58-60 parts of HDPE, 4-6 parts of nano-montmorillonite, 1-2 parts of benzoyl peroxide, 2-5 parts of BHT heat stabilizer and antioxidant, 2-5 parts of maleic anhydride grafted polyethylene, 0.2-1 parts of magnesium stearate, and 0.3-0.8 parts of epoxidized soybean oil; It includes a fireproof layer, which is composed of the following components in parts by weight: 45-55 parts of HDPE and 5-15 parts of a phosphate-based environmentally friendly flame retardant; It includes a heat-insulating layer, which is composed of the following components in parts by weight: 45-55 parts of HDPE, 5-10 parts of lignin fiber, and 5-10 parts of a bio-based foaming agent mixed with sodium bicarbonate and citric acid; The surface layer is composed of the following components in parts by weight: 58-60 parts of HDPE and 1-3 parts of zinc oxide.
2. The PEF composite board according to claim 1, characterized in that: The lignin fibers in the thermal insulation layer are heat treated at 150-180° C. for 2 hours and then subjected to alkali treatment; The bio-based foaming agent mixed with sodium bicarbonate and citric acid comprises sodium bicarbonate and citric acid in a molar ratio of 1:
1.
3. The PEF composite board according to claim 1, characterized in that: The nano-montmorillonite is a nano-silicate with its surface modified by cations; The BHT heat stabilizer and antioxidant is 2,6-di-tert-butyl-4-methoxyphenol.
4. The PEF composite board according to claim 1, characterized in that: The phosphate-based environmentally friendly flame retardant is selected from triphenyl phosphate, diphenyl phosphate or a mixture thereof.
5. The PEF composite board according to claim 1, characterized in that: The grafting degree of the maleic anhydride grafted polyethylene is 0.5-2%.
6. The PEF composite board according to claim 1, characterized in that: The zinc oxide is used as an anti-ultraviolet agent, and its particle size is below 100 nanometers.
7. A method for preparing a PEF composite board as claimed in claim 1, characterized in that: The following steps are involved: a) High-pressure polyethylene (HDPE), nano-montmorillonite, BHT heat stabilizer and antioxidant, epoxy soybean oil, magnesium stearate, maleic anhydride grafted polyethylene, phosphate ester environmentally friendly flame retardant, bio-based foaming agent (a mixture of sodium bicarbonate and citric acid), lignin fiber, and zinc oxide are accurately weighed in proportion; b) putting the components of the base layer: HDPE, nano-montmorillonite, BHT, epoxy soybean oil, magnesium stearate, maleic anhydride grafted polyethylene, and benzoyl peroxide into a twin-screw extruder and melting and mixing at a high temperature of 190-220° C.; c) putting the components of the fireproof layer: HDPE and phosphate-based environmentally friendly flame retardant into a twin-screw extruder for melt mixing; d) putting the components of the insulation layer: HDPE, pretreated lignin fiber, and bio-based foaming agent into a twin-screw extruder for melt mixing, and generating uniform bubbles through the reaction of sodium bicarbonate and citric acid; e) putting the components of the surface layer: HDPE and zinc oxide into a twin-screw extruder for melt mixing; f) injecting each layer of the mixture into a high-pressure mold in turn, strictly controlling the foaming temperature and pressure of each layer to achieve fine and uniform bubble distribution; g) After forming, the product is cooled and cut into required sizes, and a protective layer is sprayed on the surface, wherein the protective layer is an acrylic or polyurethane coating.
8. The method for preparing a PEF composite board according to claim 7, characterized in that: The lignin fibers in the thermal insulation layer are heat treated at 150-180° C. for 2 hours and then subjected to alkali treatment.
9. The method for preparing a PEF composite board according to claim 7, characterized in that: Step g is carried out by a water cooling or air cooling system.
10. The method for preparing a PEF composite board according to claim 7, characterized in that: The preparation of maleic anhydride grafted polyethylene comprises the following steps: Step 1: HDPE is used as the matrix material, maleic anhydride is used as the grafting monomer, and BPO is used as the free radical initiator. HDPE and BPO are mixed evenly in a mass ratio of 100:1 under dry conditions; Step 2: Put the mixture into a twin-screw extruder and perform melt mixing at a high temperature of 190-220°C to ensure that the HDPE is completely melted and fully mixed with the initiator; Step 3: During this process, maleic anhydride is gradually added to make it evenly dispersed in the HDPE matrix. The grafting reaction is controlled by adjusting the screw speed and temperature curve of the extruder. The reaction time is 10-30 minutes.
Citation Information
Patent Citations
Thermal insulation raw material, thermal insulation material and multilayered composite material
CN104558745A
Moisture-proof heat-insulation composite board, preparation method thereof and moisture-proof heat-insulation board A
CN115847930A
Flame-retardant heat-insulating EPE building material and preparation method thereof
CN118269431A
Polyethylene composite flame-retardant waterproof material and preparation method thereof
CN118834461A
Polyethylene-based eco-friendly multi-layer film with excellent gas barrier properties and method for manufacturing the same
KR102416093B1
Cited By
Flame-retardant nylon material, preparation method thereof and magic tape
CN120737599A